A Novel Marker to Predict Early Recurrence After Atrial Fibrillation Ablation: The Ablation Effectiveness Quotient. (25th February 2015) - WYNN, GARETH J.; DAS, MOLOY; BONNETT, LAURA J.; HALL, MARK C.S.; SNOWDON, RICHARD L.; WAKTARE, JOHAN E.P.; MODI, SIMON; TODD, DERICK M.; GUPTA, DHIRAJ
Ablation Effectiveness Quotient Introduction Inability to predict clinical outcome despite acutely successful pulmonary vein isolation (PVI) remains the Achilles' heel of atrial fibrillation ablation (AFA). Arrhythmia recurrence is frequently due to recovery of radiofrequency (RF) ablation lesions believed to be complete at the original procedure. Objectives We hypothesized that a high ratio between post‐AFA levels of serum high sensitivity cardiac troponin T (HScTnT), a highly specific marker of acute myocardial injury, and duration of RF application (the ablation effectiveness quotient, AEQ) would indicate effective ablation and correlate with early clinical success. Methods We prospectively measured HScTnT levels in 60 patients (42 [70%] male, 22 [37%] with paroxysmal AF [PAF], mean age 62.5 ± 10.6 years) 12–18 hours after AFA and calculated the AEQ for each. Patients were followed‐up with ECGs and Holter monitors for recurrence of atrial tachyarrhythmia (AT). Results Early recurrence of AT within 6 months occurred in 22 (37%). AT recurrence was not significantly related to left atrial size or comorbidities, nor to RF time or HScTnT level. Mean AEQ was significantly lower in those with recurrence than those without (0.35 ± 0.14 ng/L/s vs. 0.45 ± 0.18 ng/L/s), P = 0.02. Subgroup analysis showed this finding was due to patients with PAF in whom early significance was maintained to one year, with an AEQ >0.4 ng/L/s having 75% sensitivity and 90% specificity in predicting freedom from AT. Conclusion A high AEQ correlates well with freedom from AT in patients with PAF in both the short and medium term. If confirmed in further studies, AEQ may become a useful marker of risk of AT post‐AFA.